What future are you talking about? Efficacy of Life Design Psy-Lab, as career guidance intervention, to support university students’ needs during COVID-19 emergency - Camussi, Elisabetta; Meneghetti, Daria; Sbarra, Maria Luisa; Rella, Riccardo; Grigis, Paolo; Annovazzi, Chiara (Frontiers in Psychology, 2023)
The pandemic increased world’s uncertainty, and led to deep change in daily habits, generating disorientation, and inevitably affecting people life and professional plans. Young adults and students’ future perspective and satisfaction with life were widely affected, especially for those facing school/work transitions. Nevertheless, intervening in this complex period to support students required professionals to adapt and work navigating “on sight”, especially when little literature was available. After suspending all in-person activities because of Covid-19 emergency, the Life Design Psy-Lab, a career guidance service from Bicocca University (Milan, Italy), implemented a thematic online group intervention, in response to students’ needs during this crisis. Based on the theoretical model of Life Design, the intervention was performed by career counselling psychologists and was focused on fostering students’ development of skills and mindset to face complexity and unpredictability. The final goal was to help students shift their time perception from an uncertain present to a more optimistic future scenario. This paper will focus on the description of the intervention and its impact assessed by pre and post online questionnaires. Data show how students participating in the intervention increased their precepted level in a set of skills to face change and complexity, namely career adaptability, courage, time perspective and resilience. Also, data show how the intervention strengthened students' life satisfaction. This paper will thus contribute to expand the growing yet still newborn set of knowledge about career guidance interventions in times of Covid-19 emergency, specifically addressing the issue of design interventions that can improve young adults’ skills to visualize and project present and future for themselves, especially during uncertain times.